Molecular composition and pathology of entheses on the medial and lateral epicondyles of the humerus: a structural basis for epicondylitis. Issue 9 (12th August 2004) - Milz, S; Tischer, T; Buettner, A; Schieker, M; Maier, M; Redman, S; Emery, P; McGonagle, D; Benjamin, M
Abstract : Objectives: To improve the understanding of epicondylitis by describing the normal structure and composition of the entheses associated with the medial and lateral epicondyles and their histopathology in elderly cadavers. Methods: Medial and lateral epicondyles were obtained from 12 cadavers. Six middle aged cadavers (mean 47 years) were used to assess the molecular composition of "normal" entheses from people within an age range vulnerable to epicondylitis. Cryosections of epicondylar entheses were immunolabelled with monoclonal antibodies against molecules associated with fibrocartilage and related tissues. A further six elderly cadavers (mean 84 years) were used for histology to assess features of entheses related to increasing age. Results: Tendon entheses on both epicondyles fused with those of the collateral ligaments and formed a more extensive structure than hitherto appreciated. Fibrocartilage (which labelled for type II collagen and aggrecan) was a constant feature of all entheses. Entheses from elderly subjects showed extensive microscopic damage, hitherto regarded as a hallmark of epicondylitis. Conclusions: Fibrocartilage is a normal feature and not always a sign of enthesopathy. Furthermore, pathological changes documented in patients with epicondylitis may also be seen in elderly people. The fusion of the common extensor and flexor tendon entheses with those of the collateral ligaments suggests that the latter may be implicated as well. This may explain why pain and tenderness in epicondylitis may extend locally beyond the tendon enthesis and why some patients are refractory to local treatments.